2012
DOI: 10.1186/1532-429x-14-10
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automatic segmentation of myocardium at risk in T2-weighted cardiovascular magnetic resonance

Abstract: BackgroundT2-weighted cardiovascular magnetic resonance (CMR) has been shown to be a promising technique for determination of ischemic myocardium, referred to as myocardium at risk (MaR), after an acute coronary event. Quantification of MaR in T2-weighted CMR has been proposed to be performed by manual delineation or the threshold methods of two standard deviations from remote (2SD), full width half maximum intensity (FWHM) or Otsu. However, manual delineation is subjective and threshold methods have inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 21 publications
(30 reference statements)
5
33
0
Order By: Relevance
“…This is in keeping with Sjogren et al [13] who showed overestimation of AAR using OAT with a mean bias of +5.3 ± 9.6% compared with manual quantification [13]. The determination of an optimal threshold and quantification of enhancement on every slice with OAT, regardless of oedema is likely to contribute to this.…”
Section: Discussionsupporting
confidence: 86%
“…This is in keeping with Sjogren et al [13] who showed overestimation of AAR using OAT with a mean bias of +5.3 ± 9.6% compared with manual quantification [13]. The determination of an optimal threshold and quantification of enhancement on every slice with OAT, regardless of oedema is likely to contribute to this.…”
Section: Discussionsupporting
confidence: 86%
“…They showed that while the overall agreement between computerized and manual methods was good, there were discrepancies in area-at-risk estimation between the manual method and their method as measured in individual patients. Johnstone’s method was further developed by Sjogren et al [22] by using a prior model of the maximal extent for the user defined culprit and based on the assumption that transmural ischemia occurs within the affected single coronary artery. By using regional analysis, their results showed improvements compared to Johnstone’s study with a mean oedema bias of -1.9±6.4% of LV volume compared to manual reference and higher degree agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, infarct size was quantified on LGE imaging using the Full-Width Half-Maximum technique (11). On the pre-discharge CMR scan, ischaemic area-at-risk (oedema) was assessed using Otsu’s Automated Technique (12) and myocardial salvage index (MSI) was calculated as the percentage of the area at risk that was not infarcted on LGE (5). If infarction was seen in >1 coronary territory in the pre-discharge CMR, this was recorded as being in the IRA territory (associated oedema and/or MVO) or the non-IRA territory with the consensus of three observers (JNK, GPM, JPG).…”
Section: Methodsmentioning
confidence: 99%